2020
DOI: 10.1088/1757-899x/852/1/012141
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of attacks and mitigations on smartphone infrastructure

Abstract: The increasing number of smartphone users will encourage competition among smartphone manufacturers in innovating and marketing their products. Such competition can create open space for attackers to understand how smartphones work and then spread threats through malicious programs. In this study, a brief review of various threats and mitigations is carried out on smartphones infrastructure, especially on several well-known brand smartphones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…5G networks are going to be deployed or have already been deployed in many cities, which are underway to change our lives. As mentioned by Setyawan et al, the number of smartphone users will reach 5.9 billion in 2025 [5]. Arshad et al reported that the number of devices on Internet will gain over 100 billion in 2025 [6].…”
Section: Introductionmentioning
confidence: 99%
“…5G networks are going to be deployed or have already been deployed in many cities, which are underway to change our lives. As mentioned by Setyawan et al, the number of smartphone users will reach 5.9 billion in 2025 [5]. Arshad et al reported that the number of devices on Internet will gain over 100 billion in 2025 [6].…”
Section: Introductionmentioning
confidence: 99%
“…3 In the era of IoT and 5G, smart cities that address the challenges of overpopulation and urbanization by real-time monitoring and controlling over the city will be more than a simple buzzword. Thus far, it is projected that the number of smartphone users will hit 5.9 billion by 2025, 4 and the number of devices on Internet will exceed 100 billion by 2025. 5 Hence, the 5G technology will provide excellent opportunities and driving force for the development of smart cities.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing coverage of the 5G network is gradually changing the way we live and connect. According to Setyawan et al (2020), smartphone users will reach 5.9 billion by 2025. The smart city concept represents a vision of urban development that enables sustainable management of urban resources on the one hand and a higher quality of life for citizens through the advanced application of technology on the other.…”
Section: Introductionmentioning
confidence: 99%